'Exploding' immaterial substances: Margaret Cavendish's vitalist-materialist critique of spirits. Issue 5 (2nd September 2016) - Wilkins, Emma
ABSTRACT: In this paper, I explore Margaret Cavendish's engagement with mid-seventeenth-century debates on spirits and spiritual activity in the world, especially the problems of incorporeal substance and magnetism. I argue that between 1664 and 1668, Cavendish developed an increasingly robust form of materialism in response to the deficiencies which she identified in alternative philosophical systems – principally mechanical philosophy and vitalism. This was an intriguing direction of travel, given the intensification in attacks on the supposedly atheistic materialism of Hobbes (whom she knew personally and to whom she was intellectually indebted). While some scholars claim that Cavendish's views were not formed out of extensive engagement with contemporary thinkers, I suggest that, on the contrary, Cavendish engaged very closely with the views of More, Hobbes and others – including the vitalist thinker Johannes Baptista van Helmont and the mechanical philosopher Henry Power – on the subject of spirits and spiritual activity.